The educational effectiveness of the attitude approach model to the compliance of pregnant women consuming Fe - Halisah, Halisah (Innovative Approaches in Health Science Journal, 2025)
Background: Compliance of pregnant women in taking iron (Fe) tablets is an important factor in preventing pregnancy anemia. However, compliance rates are still low in some areas. An educational approach based on local culture such as SIPAKATAU (mutual respect in Bugis-Makassar culture) is considered to be able to increase the role of the family in supporting regular Fe consumption. Methods: This study used a quasi-experimental design with a post-test only control group design approach. The sample consisted of 32 pregnant women who were randomly divided into two groups: the intervention group that was educated with the SIPAKATAU approach model and the control group that did not receive the education. Data analysis used Fisher's Exact Test and Odds Ratio (OR) tests. Results: Results showed that pregnant women who received education with the SIPAKATAU approach model had a 2.667 times higher compliance rate in taking Fe tablets compared to pregnant women who did not receive the education (p = 0.00; OR = 2,667). Conclusion: Education with the SIPAK approach model is effective in increasing the adherence of pregnant women in consuming Fe tablets. The application of this model is recommended for midwives to optimize the role of the family as companions and supervisors in iron supplementation programs during pregnancy.